Introduction (EAAE Annual Conference Proceedings, 2023)
The conference, entitled “New Dimensions”, focused primarily on the increase in scale and the overlapping of disciplines in the practice and education of architects, urbanists and landscape architects. The Faculty of Architecture CTU considers the overlapping of these disciplines in its educational programmes and wants to discuss and share its experience on this topic.